Thyroid-stimulating hormone (TSH) and pregnancy outcome in patients undergoing in vitro fertilization (IVF) - Mohammad Abedi Samakoosh; Zinatosadat Bouzari; Shahla Yazdani; Fatemeh Rashidi; Masoumeh Golsorkhtabaramiri (Babol University of Medical Sciences, 2015)
Introduction: Subclinical hypothyroidism is related to poor outcome of pregnancy, which is reported in more recent researches. The aim of this study was to determine the correlation between pre-conception of thyroid-stimulating hormone (TSH) level and pregnancy outcomes in patients undergoing in vitro fertilization (IVF).  Methods: This retrospective cohort study was done on 115 IVF candidate patients undergoing long protocol of ovulation induction that became pregnant from 2007 to 2012. Pregnancy outcomes, including abortion rate, termination age of pregnancy and birth weight in women with low pre-conception TSH (≤2.5 mIU/L) and high pre-conception TSH (>2.5 mIU/L) were compared with each other. Results: Among 115 pregnancies, 30.2% of the women had pre-conception TSH >2.5 mIU/L. Preterm delivery (<32 weeks) was higher in patients with a pre-conception TSH >2.5 than them with a pre-conception TSH ≤2.5 (P= 0.044). There was no statistically significant difference in abortion, pregnancy termination, and birth weight between two groups. A pre-conception thyroid-stimulating hormone level >2.5 mIU/L is associated with a lower gestational age at delivery in women undergoing in vitro fertilization. Conclusion: The results of this research indicated that a pre-conception thyroid-stimulating hormone level >2.5 associated with preterm labor in women undergoing IVF. Therefore, it is suggested that screening for hypothyroidism before IVF could be have significant public health implications.